Solution for Problem 1.7.3

Solve for xf(x) = 3x2 - x - 4  

Solve

Step

Factor out the 2 first Multiply out to verify

Now complete the square* inside parenthesis
To Remove -1/36 from parenthesis, Multiply it by 3.
(x - 1/6)2 = x2 - (1/3)x + 1/36

3(1/36) - 4 = 1/12 - 48/12 = -49/12

Vertex (1/6, -49/12)

Vertex is (h,k)
This means the vertex is shifted 1/6 units right and -49/12 units up from the origin.
*Check out  completing the square for help with this step.


Click Icon for Quadratic Grapher.